DE-ZINCING OF LEAD-COPPER SULPHIDE MINERALS FLOTATION - NGURAH ARDHA (Puslitbang tekMIRA, 2011)
Typical lead-copper-zinc sulphide minerals were found hard to be separated selectively by froth flotation in the plant practice operation due to part of sphalerite was progressively entrapped into lead-copper bulk flotation. A series of de-zincing on lead-copper flotation tests has been conducted in the laboratory to reduce unwanted zinc content. Dosages variation of common sphalerite depressant such as sodium cyanide, sodium bisulphite combined with zinc sulphate were employed in addition to flotation time and pH regula- tors alteration. The flotation results exhibit that lesser zinc component is still presence in lead-copper concentrate due to intricate association of the minerals particle. However, this study in general performs tendency of de-zincing requirement as well as improvement of lead-copper recovery by increasing con- sumption of such depressant agent and may regrind otherwise.